2023
DOI: 10.1186/s12891-023-06709-y
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical analysis of different osteosynthesis configurations in the pin and plate fixation method for distal humerus fractures

Abstract: Distal humerus fractures commonly occur in adults with low bone mineral density causing major technical challenges for orthopedic surgeons. Persian fixation method was introduced as a novel technique to stabilize small fragments in comminuted distal humerus fractures using a set of K-wires and a reconstruction plate. The present study aims to measure this technique's stiffness and stability of this technique and analyze the effect of influential parameters with numerical simulation and biomechanical testing on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…In the present study, out of the three investigated pin configurations, groups I and III were included with the aim to ascertain the results of our previous FE study regarding the effect of K-wire diameter in the overall fixation structure stiffness 22 . Group II was added to explore a new factor (i.e., K-wire arrangement) and whether this factor can affect the structure stiffness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, out of the three investigated pin configurations, groups I and III were included with the aim to ascertain the results of our previous FE study regarding the effect of K-wire diameter in the overall fixation structure stiffness 22 . Group II was added to explore a new factor (i.e., K-wire arrangement) and whether this factor can affect the structure stiffness.…”
Section: Discussionmentioning
confidence: 99%
“…Also, two finite element (FE) studies have been carried out regarding the Persian fixation technique which investigated the biomechanical behavior of the Persian fixation technique under various loading conditions. Hakiminejad et al 22 modeled different configurations of K-wire number, diameter, and plate position to analyze their effects on fixation stiffness. Another FE study by Jitprapaikulsarn and others found their tested variation of the method to have overall comparable stability to the conventional methods except in internal rotation loading 23 .…”
Section: Introductionmentioning
confidence: 99%